FINANCIAL REPORT ASSISTANCE FOR MICRO BUSINESS IN ILIR BARAT II DISTRICT, PALEMBANG CITY - Liliana Liliana; Ariodillah Hidayat; Anton Indra Budiman; Siti Rohima; Irvi Givelyn; Xenaneira Shodrokova (Universitas Muhammadiyah Tapanuli Selatan, 2023)
Micro, Small and Medium Enterprises (MSMEs) have the potential to be developed because they contribute to the economy in Indonesia. MSMEs have a significant role in the country's economic growth The main objective of UMKM is basically to gain profits by increasing production efficiency, but in practice it often encounters many obstacles and problems, one of which is the problem of financial management. Good financial recording is very necessary because good financial recording and reporting can be used as a basis for analysis for managerial decisions that can affect business progress. The model of service activities is carried out by the method of coaching skills through the provision of materials and assistance. The result of the activity was that the participants had understood the basic material regarding financial statements, as well as provided assistance toÂ find out firsthand the problems faced by respondents and solutions to overcome these problems.